2013
DOI: 10.1590/s1984-70332013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive characteristics of citrus rootstocks grown under greenhouse and field environments

Abstract: -The aim of the present study was to evaluate the possible effect of environmental factors on meiosis, meiotic index, pollen viability and in vitro germination of pollen from stock plants of the rootstocks Trifoliate, 'Swingle', 'Troyer', 'Fepagro C13', 'Fepagro C37' and 'Fepagro C41' grown 28%, 56.23% and 74.74%, and, in the greenhouse, 64.25%, 41.41% and 66.71%, respectively. As temperature oscillations were higher in the greenhouse than in the field, we suggest that this negatively affects the reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This allows us to infer that this variation in amplitude influences the ploidy level of the evaluated seedlings, but it is not possible, however, to identify the exact factor, or factors, that resulted in polyploidization. Guerra et al (2013) suggested thermal amplitude as the likely factor that changed the male fertility in the same mother plants used in this study; those authors observed a lower percentage of normal meiotic cells and lower viability and in vitro germination of pollen grains in the plants grown in greenhouse compared to the field. Therefore, some factor present in the greenhouse conditions, like temperature and thermal amplitude, damaged the male fertility and could be promoting the polyploidization of plants in this environment.…”
Section: Resultsmentioning
confidence: 58%
“…This allows us to infer that this variation in amplitude influences the ploidy level of the evaluated seedlings, but it is not possible, however, to identify the exact factor, or factors, that resulted in polyploidization. Guerra et al (2013) suggested thermal amplitude as the likely factor that changed the male fertility in the same mother plants used in this study; those authors observed a lower percentage of normal meiotic cells and lower viability and in vitro germination of pollen grains in the plants grown in greenhouse compared to the field. Therefore, some factor present in the greenhouse conditions, like temperature and thermal amplitude, damaged the male fertility and could be promoting the polyploidization of plants in this environment.…”
Section: Resultsmentioning
confidence: 58%
“…Mature pollen was analyzed, of which the stained grains were considered viable and wrinkled or colorless grains unviable (Singh 1993). About 1000 mature pollen grains per plant were counted in four flowers per plant (250 pollen grains per plant), following the protocol established and used (Dahmer et al 2008, Guerra et al 2013, Krycki et al 2016. The pollen viability estimate was calculated by the percentage of viable grains: number of grains considered viable divided by the total number of grains multiplied by 100 (Tedesco et al 2019).…”
Section: Meiotic Chromosome Pairing and Pollen Viability Analysismentioning
confidence: 99%
“…Pollen grains were considered fertile when full and well stained, while those unstained or weakly stained, were considered sterile (not viable unviable) (Singh 1993). One thousand mature pollen grains were counted in four flowers per plant, following the protocol already established and widely used (Dahmer et al 2008, Guerra et al 2013.…”
Section: Pollen Viability Analysismentioning
confidence: 99%